INDUSTRI KELAPA INDONESIA: KINERJA DAN PERSPEKTIF PENGEMBANGAN MENUJU PENINGKATAN NILAI TAMBAH DAN DAYA SAING (Forum Penelitian Agro Ekonomi, 2023)
Coconut commodity has a strategic role in the country's foreign exchange earnings, providing employment and increasing farmers' income. In 2020, the value of Indonesia's coconut exports reached US$890 million, with a total export volume of 1.8 million tons. The most significant export value is processed coconut oil, namely crude coconut oil and semi-finished coconut oil, by 50% of other processed coconut products. The export value of processed crude coconut oil was 29% or US$254.9 million, and semi-finished coconut oil was 21% or US$188.1 million. This paper reviews the performance and problems of coconut Indonesia's industry and identifies opportunities for its development. The coconut industry performance has issues from upstream to downstream. The upstream problems are low productivity, old plants, limited capital resources, damaged plants, and decreasing land area. The downstream issues are the need for more innovation in coconut products, coconut exports dominated by fresh coconuts and their derivatives, and the decline in export performance for processed crude and semi-finished oil products, which are the mainstay of coconut exports. Innovation and technology are necessary to enhance the coconut industry's performance. Produce ready-to-use products that are increasingly in demand in global and domestic markets. Productivity improvements, production costs, and quality are determinants of the competitiveness and yield of coconut exports.